Nutrigenomic and Nutritional Analyses Reveal the Effects of Pelleted Feeds on Asian Seabass (Lates calcarifer). - Si Yan Ngoh; Daniel Tan; Xueyan Shen; Purushothaman Kathiresan; Junhui Jiang; Woei Chang Liew; Natascha May Thevasagayam; Hsiao Yuen Kwan; Jolly M Saju; Sridatta R S Prakki; Chin Heng Goh; Hong Ching Wong; et al. (PLoS ONE)
As nutrition-related expenses constitute the majority of the costs for aquaculture farms, it is essential for them to use feeds that provide an ideal combination of nutrients for the species of choice. In this study, the relative effect of consuming three different pelleted feeds (B, C and D) in comparison to frozen baitfish (A; control) were compared on juvenile Asian seabass (77.3 ± 22.4g) that were selected for increased growth rate over two generations. Our objectives were: 1) to evaluate the effects of different pelleted feeds based on overall physiological changes and nutritional quality of fillets; 2) improve our understanding of the underlying mechanisms with transcriptomic analysis; 3) if possible, identify the feed type that supports the growth of these fishes without substantially reducing the nutritional quality of fillet. The growth performance, fatty acid composition of fillet, hepatic histology and transcriptome of the fishes (Groups A-D) were analyzed. The majority of fatty acids of the fillets, except γ-linolenic acid (GLA, C18:3n6), correlated significantly with the respective diets. Asian seabass fed Feed C showed highest specific growth rate (SGR) and feed conversion efficiency (FCE) with closest histology and transcriptomic profile to control, but their fillet contained the highest n6/n3 ratio. When the liver-based transcriptomes were analyzed, a complex set of differentially expressed genes were detected between groups fed pelleted feeds and controls as well as among the pellet-fed groups themselves. Significant enrichment of genes with growth-related function tallied with the morphological data measured. When compared with control (Group A), 'Biosynthesis of unsaturated fatty acids' and 'Steroid biosynthesis' pathways were significantly enriched in pellet-fed groups. Reduced goblet cell numbers were observed in the gut of pellet-fed fish compared to controls and fads6 was found to be a suitable candidate gene to separate wild-caught Asian seabass, from pellet-fed ones. These results provide insights for researchers on the various effects of feeds on the biochemistry and global gene expression of the fish and potentially for seabass farms to make more informed feed choices.